1997
DOI: 10.1111/j.1439-0396.1997.tb00855.x
|View full text |Cite
|
Sign up to set email alerts
|

The tryptophan requirement of piglets as influenced by the threonine level

Abstract: Summary The tryptophan (Trp) requirement was investigated in post weaning piglets from 5 to 10 weeks of age (7–20kg). Three feeding trials were conducted. All piglets were randomly alloted according to age, sex, weight, pre‐weaning growth and ancestry to the different dietary treatments. Ad libitum feed intake (per 6–7 pigs) and daily gain (individual) were recorded at 5 and 10 weeks (end of experiment). In the first trial 72 Belgian Landrace (BL) and 60 Piétrain × Seghers Hybrid (P × SH) piglets were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(9 reference statements)
0
4
1
Order By: Relevance
“…(1998) showed no performance response to additional Trp above 1.3 g digestible Trp/kg diet and improved gain and feed intake by increasing the Thr:Lys ratio to 0.65, but no effect of supplementing Trp when dietary Thr appeared to be limiting. The discrepancy in results between Warnants et al. (1998) and the current experiment cannot be explained, especially when these two experiments utilized a similar diet composition and used pigs of a similar weight range.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…(1998) showed no performance response to additional Trp above 1.3 g digestible Trp/kg diet and improved gain and feed intake by increasing the Thr:Lys ratio to 0.65, but no effect of supplementing Trp when dietary Thr appeared to be limiting. The discrepancy in results between Warnants et al. (1998) and the current experiment cannot be explained, especially when these two experiments utilized a similar diet composition and used pigs of a similar weight range.…”
Section: Discussioncontrasting
confidence: 62%
“…This is supported by others (Jansman et al., 2000; Lynch et al., 2000) who reported that wheat‐barley‐based diets may need to have a 0.21 Trp:Lys ratio for optimal performance. In contrast, Warnants et al. (1998) showed no performance response to additional Trp above 1.3 g digestible Trp/kg diet and improved gain and feed intake by increasing the Thr:Lys ratio to 0.65, but no effect of supplementing Trp when dietary Thr appeared to be limiting.…”
Section: Discussionmentioning
confidence: 81%
“…The optimal ratio of tryptophan to lysine in this experiment was about 17:100; it should be pointed out, however, that the dietary lysine concentration, being 12.3 g per kg diet, was about 10% and 30% higher than the levels recommended by the National Research Council (1995) for the body weight categories from 10 to 20 kg (11.5 g lysine recommended per kg diet) and over 20 kg (9.5 g lysine recommended per kg diet), respectively. Although, the optimal ratio of tryptophan to lysine, thus, might be underestimated, it is higher than optimal ratios reported in the literature ranging between 0.14 and 0.15 (Borg et al, 1987;Burgoon et al, 1992;Warnants et al, 1998).…”
Section: Discussionmentioning
confidence: 58%
“…In the body weight range between 5 to 35 kg, the stated tryptophan requirements for maximum performance vary widely. In most studies tryptophan concentrations between 1.2 und 1.6 g per kg feed were sufficient for maximum performance (Zimmerman, 1975;Leibholz, 1981;Sato et al, 1987;Batterham and Watson, 1985;Wahlstrom et al, 1985;La Rue et al, 1985;Borg et al, 1985a;Borg et al, 1987;Han et al, 1993;Henry et al, 1986;Warnants et al 1998). An older study (Boomgaardt und Baker, 1973) calculated an even lower tryptophan requirement of less than lg per kg feed.…”
Section: Introductionmentioning
confidence: 99%
“…However, when following this procedure, the optimum ratio (T: L opt ) tends to be overestimated because the true optimum ratio lies between T: L opt and the nearest ratio tested below (T: L opt À 1 ). It is, (Lougnon, 1981; probably in one of the experiments of Batterham and Watson, 1985), threonine (Lougnon, 1984;Warnants et al, 1998;Eder et al, 2001) or crude protein (Mö hn and Susenbeth, 1994) in the diets were limiting. b Initial and final body weight of animals, at which the beginning of the plateau phase was observed.…”
Section: Methodsmentioning
confidence: 99%